Theorising occupational therapy practice in diverse settings - Creek, Jennifer; Pollard, Nick, MSc(OT); Allen, Michael (Sociologist) (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Practice theory provides a way of understanding everyday life, but until now its application in occupational therapy has not been much developed. Theorising Occupational Therapy Practice in Diverse Settings draws on practice theory to explore the conditions for occupational therapy practice in a variety of clinical and non-traditional settings. With numerous case examples, this is an important new text for students and practitioners of occupational therapy. It is relevant both for those working in, or preparing for, placements in mainstream health and social care services, or in community interest companies, charities and social enterprises"--
History and development of theory for occupational therapy practice / Jennifer Creek and Michael Allen -- Managerialism and health services / Jennifer Creek -- Space-time, temporality and professional roles / Kate Sherry, Jennifer Creek and Michael Allen -- Space-time, place and working contexts / Kate Sherry and Anri-Louise Oosthuizen -- The current position of occupational therapy theory and practice / Nick Pollard -- Access / Elly Badcock, Elise Bromann Bukhave and Jennifer Creek -- Resources / Temple Moore and Jennifer Creek -- Change in occupational therapy / Anna Carreira De Mello, Tais Quevedo Marcolino and Nick Pollard -- Where we want to be / Nick Pollard and Jennifer Creek.
Keywords: Occupational therapy; MEDICAL / Allied Health Services / Occupational Therapy